Co-evolution of bats and viruses and how it has shaped host biology - Skirmuntt, EC (2021)
Although the general link between bats and viral diseases is clear, tracing outbreaks to their bat origins can be difficult. It is believed that the lack of symptoms in bats may be caused by their long co-evolution with viruses, their immunological traits, or evolutionary adjustments arising from endogenized viral genes.